Controversies in hormone replacement therapy (Medical Journal of Indonesia, 2001)
Deficiency of estrogen hormone will result in either long-term or short-term health problems which may reduce the quality of life. There are numerous methods by which the quality of female life can be achieved. Since the problems occuring are due to the deficiency of estrogen hormone, the appropriate method to tackle the problem is by administration of estrogen hormone. The administration of hormone replacement therapy (HRT) with estrogen may eliminate climacteric complaints, prevent osteoporosis, coronary heart disease, dementia, and colon cancer. Although HRT has a great deal of advantage, its use is still low and may result in controversies. These controversies are due to fact that both doctor and patient still hold on to the old, outmoded views which are not supported by numerous studies. Currently, the use of HRT is not only based on experience, or temporary observation, but more on evidence based medicine. (Med J Indones 2001; 10: 182-6)